How the Copper Dopant Alters the Geometric and Photoelectronic Properties of the Lead‐Free Cs2AgSbCl6 Double Perovskite. Issue 8 (9th July 2021) - Yu, Gan; Xue, Shaoming; Yin, Ruotong; Wu, Qiaoqian; Gao, Tianhao; Song, Yixian; Wang, Ruijie; Cong, Wei‐Yan; Guan, ChengBo; Lu, Ying‐Bo
Abstract: The Cu‐modulated lead‐free double perovskite Cs2 AgSbCl6 shows excellent photoelectric performances. Thus the distribution of Cu dopants inside Cs2 AgSbCl6 and the influence induced by them are investigated thoroughly. The variation of charge distribution and then the electronic environment around the Cu dopant are simulated, which support the preferred formation of CuAg defect in Cs2 AgSbCl6 with a nominal monovalent state. Compared with other Cu‐related defects, this configuration introduces the weakest tensile stress around the defects and the slightest distortion of the metal octahedron. Owing to the special CuAg defect, the electronic structures of Cs2 AgSbCl6 system change, e.g., the bandgap reduces manifestly, ascribing to the predominant contribution from Cu‐3d orbitals to the band edges. With the increase of concentration of Cu dopants, the bandgap of Cs2 AgSbCl6 decreases further in a monotonic but gentle way, originating from the extra interactions between the Cu‐3d orbitals. Therefore, the critical insight to understand the photoelectronic properties of Cs2 AgSbCl6 modulated by the Cu dopants is provided. Abstract : The distribution of Cu dopants inside the Cs2 AgSbCl6 lattice and their influence are investigated thoroughly. The electronic environment around Cu dopant supports the preferred formation of CuAg defect with a nominal monovalent state, introducing the weakest tensile stress and the slightest octahedron distortion. This also reduces the bandgap of Cs2 AgSbCl6 manifestly, due to the predominant contribution from Cu‐3d orbitals.